Goal prediction in 2‐year‐old children with and without autism spectrum disorder: An eye‐tracking study. Issue 6 (5th February 2018) - Krogh‐Jespersen, Sheila; Kaldy, Zsuzsa; Valadez, Annalisa Groth; Carter, Alice S.; Woodward, Amanda L.
Abstract : This study examined the predictive reasoning abilities of typically developing (TD) infants and 2‐year‐old children with autism spectrum disorder (ASD) in an eye‐tracking paradigm. Participants watched a video of a goal‐directed action in which a human actor reached for and grasped one of two objects. At test, the objects switched locations. Across these events, we measured: visual anticipation of the action outcome with kinematic cues (i.e., a completed reaching behavior); goal prediction of the action outcome without kinematic cues (i.e., an incomplete reach); and latencies to generate predictions across these two tasks. Results revealed similarities in action anticipation across groups when trajectory information regarding the intended goal was present; however, when predicting the goal without kinematic cues, developmental and diagnostic differences became evident. Younger TD children generated goal‐based visual predictions, whereas older TD children were not systematic in their visual predictions. In contrast to both TD groups, children with ASD generated location‐based predictions, suggesting that their visual predictions may reflect visuomotor perseveration. Together, these results suggest differences in early predictive reasoning abilities. Autism Res 2018, 11: 870–882 . © 2018 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: The current study examines the ability to generate visual predictions regarding other people's goal‐directed actions, specifically reaching and grasping an object, in infants and children with and without autism spectrum disorder. Results showed no differences in abilities when movement information about a person's goal was evident; however, differences were evident across age and clinical diagnoses when relying on previous knowledge to generate a visual prediction.